2004
DOI: 10.1021/ma049848o
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulation of the Water Influence on the Local Structure of Polyamide 6,6

Abstract: To understand, at a molecular scale, the effect of water on the structure of the amorphous region of polyamide 6,6 (PA6,6), atomistic molecular dynamics simulations have been carried out. Our results concerning the very local water organization relative to PA moieties agree qualitatively with a two-step sorption model. The first sorption mode seems to be saturated well below the lowest water concentration studied (5% relative to the amorphous phase). Moreover, above this saturation, the overall water organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
91
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 36 publications
10
91
0
Order By: Relevance
“…The parameters for best fits along with the amplitude-weighted average τ R for four temperatures are listed in Table. 1. As we can see in Table 1, we have an abrupt increase in the structural relaxation time as the glass transition temperature T g (330 K) as calculated from our atomistic model 26 approaches.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The parameters for best fits along with the amplitude-weighted average τ R for four temperatures are listed in Table. 1. As we can see in Table 1, we have an abrupt increase in the structural relaxation time as the glass transition temperature T g (330 K) as calculated from our atomistic model 26 approaches.…”
Section: Resultsmentioning
confidence: 66%
“…The distance between the hydrogen of the donor group and the acceptor O has to be <0.297 nm 3 and the donor-hydrogen-acceptor angle >130°. 26 To calculate the enthalpy (∆H) of HB breaking, we adopted the model proposed by Schroeder and Cooper 6 which relates ∆H to the bonded amide fraction (X b ). The equilibrium between the hydrogen-bonded and nonbonded amides can be represented by (NH···OdC) bonded T (NH) free + (OdC) free (1) with an associated equilibrium constant K given by…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics (MD) is an attractive technique for gaining insights into RO membrane features such as polymer configuration, free volume distribution, and transport phenomena [8][9][10][11]. Indeed, it offers unique opportunities to connect some macroscopic properties to a microscopic description of the physical phenomena involved in the separation.…”
Section: Introductionmentioning
confidence: 99%
“…,26,27 Atomistic molecular dynamic simulations that were performed for PA66 have shown that the fraction of "unbound" water molecules that do not share hydrogen bonds with any amide group at a given time is only 20% for 5% absorbed water and increases to 40% for 10% absorbed water 27. Thus, a very broad distribution of the frequency of molecular motions of D 2 O in PA46, which is observed below 0 °C, is due to a variety of hydrogen bonds formed, a slow exchange between neighboring D 2 O molecules, and heterogeneous mobility of PA46 chains in the amorphous phase.Fig.…”
mentioning
confidence: 99%